Rapid formation of non-native contacts during the folding of HPr revealed by real-time photo-CIDNP NMR and stopped-flow fluorescence experiments. - Canet, D; Lyon, C; Scheek, R; Robillard, G; Dobson, C; Hore, P; van Nuland, N (2003)
We report the combined use of real-time photo-CIDNP NMR and stopped-flow fluorescence techniques to study the kinetic refolding of a set of mutants of a small globular protein, HPr, in which each of the four phenylalanine residues has in turn been replaced by a tryptophan residue. The results indicate that after refolding is initiated, the protein collapses around at least three, and possibly all four, of the side-chains of these residues, as (i) the observation of transient histidine photo-CIDNP signals during refolding of three of the mutants (F2W, F29W, and F48W) indicates a strong decrease in tryptophan accessibility to the flavin dye; (ii) iodide quenching experiments show that the quenching of the fluorescence of F48W is less efficient for the species formed during the dead-time of the stopped-flow experiment than for the fully native state; and (iii) kinetic fluorescence anisotropy measurements show that the tryptophan side-chain of F48W has lower mobility in the dead-time intermediate state than in both the fully denatured and fully native states. The hydrophobic collapse observed for HPr during the early stages of its folding appears to act primarily to bury hydrophobic residues. This process may be important in preventing the protein from aggregating prior to the acquisition of native-like structure in which hydrophobic residues are exposed in order to play their role in the function of the protein. The phenylalanine residue at position 48 is likely to be of particular interest in this regard as it is involved in the binding to enzymes I and II that mediates the transfer of a phosphoryl group between the two enzymes.